MONITORAMENTO DE MOSCAS-DAS-FRUTAS COM DIFERENTES ATRATIVOS EM POMAR DE CITROS EM PIRACICABA-SP, BRASIL - Dias, Maria Cristina Rocha; Arthur, Valter (REVISTA DE AGRICULTURA, 2015)
MONITORAMENTO DE MOSCAS-DAS-FRUTAS COM DIFERENTES ATRATIVOS EM POMAR DE CITROS EM PIRACICABA-SP, BRASIL